Melanoblasts but not melanocytes decrease in number in human epidermis of idiopathic guttate hypomelanosis - Tomohisa Hirobe; Hisao Enami (Wolters Kluwer Medknow Publications, 2018)
Background/Objective: Idiopathic guttate hypomelanosis (IGH) is a common disease that appears mainly in trunk, arms, and legs. IGH is a benign leukoderma characterized by multiple, hypo- or depigmented discrete macules. Although melanocytes have been reported to decrease in number in the IGH macules, changes in melanoblast number are not known. Moreover, satisfactory therapies for this disease have not been established. In this study, we investigated the presence of melanoblasts in the IGH macules, and tried to treat the IGH macules by mini-punch grafting using a machine (mMG) in combination with narrow-band ultraviolet B (NB-UVB) therapy. Methods: Mini-punch biopsies of the lesional skin of five patients (11-72-year-old men and woman) were fixed and processed to dopa and combined dopa-premelanin reactions to detect melanocytes and melanoblasts. Results: Although similar melanocyte density was observed in the lesional epidermis compared with the normal epidermis, melanoblast density was dramatically decreased. Moreover, epidermal melanin accumulation was greatly reduced in the lesional skin. For the treatment of the IGH macules, numerous mini-punch biopsies were removed from both recipient lesional skin and donor normal scalp skin, and then the donor biopsies were placed into the holes of the lesional skin. After 1 week, we started to expose NB-UVB to the lesional skin and continued the exposures. Excellent color-matched repigmentation was soon obtained. Conclusion: These results suggest that melanoblast proliferation and/or differentiation in addition to the melanosome transfer are defected in IGH, and the mMG and NB-UVB can support the excellent color-matched repigmentation. Keywords: Idiopathic guttate hypomelanosis, Melanoblast, Melanocyte, Skin, Transplantation